Legal Aspects of Protection of Cultural Heritage Objects in Cisaat Village, Subang Regency, West Jawa - Martini; Dian Alfia Purwandari (Journal of Legal and Cultural Analytics, 2023)
The territory of Indonesia is rich in historical relics of high value as remnants of past glory protected by law. one of them is the historical relics of cultural heritage sites located in Cisaat Village, Subang Regency, West Java. The purpose of the study was to determine whether the cultural heritage site in Cisaat village met the criteria as a cultural heritage and looked at the aspects of legal protection of sites in the cisaat area as well as the community's participation in the maintenance and protection of cultural heritage objects. This research is carried out using qualitative methods with a normative juridical approach is an approach by prioritizing and based on the main legal material by examining theories, concepts, legal principles and laws and regulations, including the results of court decisions related to this research supported by observation and interviews. The results showed that the historical relics contained in the cissat met the criteria based on the regulations that apply as cultural heritage objects.